The dual margin of Chinese agricultural products export to Japan - Lingling, Wu; Fuli, Chen; Fenghe, Zhang (Management and Entrepreneurship: Trends of Development, 2021)
The purpose of the article is to investigate the reasons for the decline in trade activity between China and Japan, considering the fact that China is the largest source of Japanese agricultural products imports. Agricultural products trade plays an important role in the economic and trade relations between China and Japan, and the proportion of China's agricultural products exports to Japan's exports is increasing year by year. However, after 2013, China's agricultural exports to Japan have shown a downward trend year by year. What are the reasons for this change in trade? What is the structure of China's agricultural exports to Japan? This is a problem that must be understood. This article uses the HS4 quantile code data of China's agricultural exports to Japan from 2010 to 2019 by the United Nations Commodity Trade Statistics Database (UN Comtrade), and applies the binary marginal decomposition method to analyze China's agricultural exports to Japan. The results show that China's agricultural exports to Japan In export growth, the marginal contribution of expansion is weak, while the marginal contribution of intensive is larger. After further decomposing the intensive margin into the quantity margin and the price margin, it is found that the growth of China's agricultural exports to Japan is mainly due to the rapid growth of the quantity margin, while the price margin does not contribute much to export growth. In the future, if China wants to expand its exports of agricultural products to Japan, it must become familiar with and adapt to the access standards of the Japanese market as soon as possible, increase the added value of agricultural products, and enhance the comprehensive competitiveness of agricultural exports to Japan.JEL Classification: F1 F12, F14.